Perceived relevance of oral biology: a comparative study among dental interns and faculty - Shakeel, Sadia; Jahangir, Kaynat; Fahim, Ayesha; Shahid, Tayyaba Nayab; Azhar, Ahmad; Chaudhry, Ammara (Journal of University Medical & Dental College, 2023)
Background & Objective: This study aims to compare and examine the distinctive perspectives of dental trainees and distinguished faculty members toward the significance of oral biology subject for dentistry, clinical training, and dental education. Methodology: A prevalidated questionnaire consisting of two sections was distributed through Google Forms and handouts to dental interns and faculty members of basic and clinical departments of different dental institutes and hospitals oh Punjab. The data was collected and statistically analyzed using IBM-SPSS version 25. The chi-square test was applied to check the significance of questions regarding perception of oral biology. A p-value of less than 0.05 was considered as the threshold for statistical significance. Results: Both groups perceived high relevance of oral biology towards dentistry with slightly more relevance reported by dental interns regarding the importance of oral biology for dental education and clinical training. Regarding the data collected from clinical dental departments Oral surgery department showed the highest relevance of oral biology with dentistry whereas the Orthodontic department considered oral biology most relevant for future clinical training and practice. Conclusions: Dental faculty and interns emphasized the importance of oral biology as a discipline for dentistry, but interns reported substantial application for relevance related to future clinical training and practice.